On the predictability of phenotypic divergence in geographic isolation. (8th December 2022) - Freeman, Benjamin G; Montgomery, Graham A; Heavyside, Julian; Moncrieff, Andre E; Johnson, Oscar; Winger, Benjamin M
Abstract: Do related populations that are separated by barriers predictably evolve differences from one another over time, or is such divergence idiosyncratic and unpredictable? We test these alternatives by investigating patterns of trait evolution for 54 sister pairs of Andean forest birds that live in similar environments on either side of the arid Marañón Gap, a strong dispersal barrier for humid montane species. We measured divergence in both sexual (song and plumage) and ecological (beak size and beak shape) traits. Sexual traits evolve in a clock-like fashion, with trait divergence positively correlated with genetic distance ( r = 0.6–0.7). In contrast, divergence in ecological traits is uncorrelated or only loosely correlated with genetic distance ( r = 0.0–0.3). Thus, for geographically isolated Andean montane forest birds that live in similar environments, divergence is predictable in sexual traits, but not for ecological traits. This means that sexual trait divergence occurs independently of adaptive ecological divergence within the mega-diverse tropical Andean avifauna. Last, we show that variation in genetic divergence across a biogeographic barrier is associated with traits that are proxies for species' opportunities for dispersal (low elevation limit and elevational niche breadth), but not with traits that are proxies for species' dispersal abilities (hand-wing index and foraging strata).